Proceedings of the 2nd Workshop on Argumentation Mining 2015
DOI: 10.3115/v1/w15-0508
|View full text |Cite
|
Sign up to set email alerts
|

Argument Extraction from News

Abstract: Argument extraction is the task of identifying arguments, along with their components in text. Arguments can be usually decomposed into a claim and one or more premises justifying it. The proposed approach tries to identify segments that represent argument elements (claims and premises) on social Web texts (mainly news and blogs) in the Greek language, for a small set of thematic domains, including articles on politics, economics, culture, various social issues, and sports. The proposed approach exploits distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…The big potential of argument extraction in political textual data has attracted many researchers in text mining. For instance, Sardianos et al [43] proposed a supervised technique, based on conditional random fields, to extract arguments and their underlying facts. They applied the method to web pages containing news and tagged speeches.…”
Section: Arguments Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The big potential of argument extraction in political textual data has attracted many researchers in text mining. For instance, Sardianos et al [43] proposed a supervised technique, based on conditional random fields, to extract arguments and their underlying facts. They applied the method to web pages containing news and tagged speeches.…”
Section: Arguments Extractionmentioning
confidence: 99%
“…As the number of digital documents has grown exponentially, almost on any topic, automated knowledge extraction methods have become popular in many sections, from science to marketing and business. Many text mining techniques deal with extracting knowledge authors represented in their texts, e.g., extracting arguments [43][44][45][46] and extracting opinions [13][14][15][16]. Knowledge extraction is usually concerned with finding and extracting the key elements from textual data (e.g., articles, short notes, tweets, blogs, etc.)…”
Section: Knowledge Extractionmentioning
confidence: 99%
“…Winkels et al 2013 [20] were among the first who experimented with unsupervised techniques in Argumentation Mining. Their results showed that pure unsupervised clustering does not yield satisfactory results [21], and Habernal and Gurevych 2015 [22] employed the new idea of word embeddings in a semi-supervised fashion for the argument identification subtask. In some cases, the results yielded a 100% improvement over previous attempts on complex online corpora.…”
Section: Related Work On Argument Identificationmentioning
confidence: 99%
“…[66,82,83,94], persuasive essays, e.g. [152,153,201,203,205], and social media [81,155,191]. Despite these, and other, developments, only few attempts, such as [204], appear to have been made at fully automating the process of building AFs from text.…”
Section: News Articles Corpusmentioning
confidence: 99%